1988
DOI: 10.1176/ajp.145.11.1396
|View full text |Cite
|
Sign up to set email alerts
|

Family planning and child mental health in China: the Nanjing Survey

Abstract: The authors studied the impact of China's one-child-per-couple family planning policy on child development in 697 preschool children in the city of Nanjing and in two rural areas surrounding Nanjing. A home-visit questionnaire survey including a Chinese version of Achenbach's Child Behavior Checklist was used. The behavior problem profiles of children who were their parents' only children and those who had siblings were compared, revealing a significant difference between girls who were only children and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The one-child policy has led to a stronger preference for boys, and disappointment over the infant's gender is a significant risk factor for perinatal depression in China (Xie et al, 2011). Furthermore, women without siblings are more likely to be affected by negative mood states (Tseng et al, 1988). Perinatal depression appears to be common in rural areas where no treatment is available and the stigma is high (Wong & Fisher, 2009).…”
mentioning
confidence: 99%
“…The one-child policy has led to a stronger preference for boys, and disappointment over the infant's gender is a significant risk factor for perinatal depression in China (Xie et al, 2011). Furthermore, women without siblings are more likely to be affected by negative mood states (Tseng et al, 1988). Perinatal depression appears to be common in rural areas where no treatment is available and the stigma is high (Wong & Fisher, 2009).…”
mentioning
confidence: 99%
“…The theory that the OCP created Little Emperors was based on the assumption that only children would be overindulged and overprotected by their two parents and four grandparents, leading the children to develop undesirable personalities and poor mental health. In response to widespread concern about Little Emperors, many studies were conducted to examine the mental health of the Chinese children, comparing them to their peers with siblings on a variety of outcomes, including psychopathology (e.g., Tao, 1998; Tseng et al, 1988; Wang & Fong, 2009; Yang, Ollendick, Dong, Xia, & Lin, 1995). The purpose of this study is to synthesize quantitatively the results of these studies of psychopathology.…”
mentioning
confidence: 99%
“…The one child per family policy employed by Chinese government might have profound effect on this. A study which compared the psychosocial outcomes between Chinese children without siblings and those with siblings found that girls who were the only children in their families had higher scores of depressive symptoms than those with siblings ( Tseng et al, 1988) . It may be argued that the higher number of siblings in the family among the Malawian sample provided an environment where the siblings interacted and provided support to each other to counteract the effects of stress.…”
Section: Discussionmentioning
confidence: 99%